FINANCIAL GOVERNANCE AND INTERNAL CONTROL SYSTEM OVERVIEW IN PIONEER VILLAGE-OWNED ENTERPRISES - Budi Barata Kusuma Utami; Rusdianto Rusdianto (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2023)
This study aims to examine financial governance and the internal control system of Village Owned Enterprises (Bumdes). This issue became important with the attention of various groups after the issuance of the Village Law Number 6 of 2014. This research is an exploratory study using a qualitative approach, and data collection using interview techniques. The results of the study show that the village-owned enterprises Barokah Handayani has a budgeting and planning process, but limited to profit target plan. Bumdes has regular bookkeeping and business reporting but the reports are not in accordance with financial reporting standards. Bumdes in business management and financial governance, has been in accordance with the principles of Bumdes Management namely cooperative, emancipation, transparent, accountable and sustainable